2020
DOI: 10.1180/clm.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of spent bleaching clay by ultrasonic irradiation and its application in methylene blue adsorption

Abstract: An effective method that combines solvent extraction with ultrasonic irradiation was developed to recycle spent bleaching clay (SBC) from modern oil refinery plants. The principle of ‘waste to treasure’ was used to achieve the regenerated SBC. Various characterization techniques were applied to analyse and compare regenerated SBC and commercial bleaching clay (CBC). The structure of the regenerated SBC did not show any obvious change compared with that of CBC, but the Brunauer–Emmett–Teller-specific surface ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Compared with the surface area of GAC, the cracked surfaces did not influence the removal efficiency of the spent adsorbent regeneration. However, a previously published study found that the carbon residues could be retained in pores and clogged the entrance of pores after the first cycle [14] and results in a reduction in the effective adsorption sites and adsorption capacity [15]. These results clearly indicate that DOWEX MB-50 is an efficient adsorbent with greater adsorptive capability and greater capacity for repeated use compared to…”
Section: Performance For Removal Of Pfas With Adsorbent Regenerationmentioning
confidence: 83%
“…Compared with the surface area of GAC, the cracked surfaces did not influence the removal efficiency of the spent adsorbent regeneration. However, a previously published study found that the carbon residues could be retained in pores and clogged the entrance of pores after the first cycle [14] and results in a reduction in the effective adsorption sites and adsorption capacity [15]. These results clearly indicate that DOWEX MB-50 is an efficient adsorbent with greater adsorptive capability and greater capacity for repeated use compared to…”
Section: Performance For Removal Of Pfas With Adsorbent Regenerationmentioning
confidence: 83%
“…Untreated SBE had a weight loss of 25.4% at 400 °C, 28.3% at 500 °C, 31.1% at 650 °C and 34.7% at 800 °C, as illustrated in Figure 1. The first weight loss of 5.97% that occurred below 150 °C can be ascribed to the thermal dehydration of trapped water molecules on the surface of materials [22]. The elimination of a majority of the coordinated water and decomposition of organic material (evaporation of volatile matter) from the SBE resulted in a quick decline in the sample weight of 17.26% at the second dehydration phase from 150 to 350 °C [13], [22], [23].…”
Section: Characterization Of Sbe and Rsbementioning
confidence: 99%
“…Therefore, much research has been devoted to studying SBEs and their various applications. [7,[9][10][11][12][13] Among these studies, the removal of textile dyes by the adsorption technique, which appears to be relatively inexpensive and effective, is widely cited. [7,11,[14][15][16][17] As has been proven, the regenerated spent bleaching earth (RSBE) materials present a strong affinity for methylene blue (MB).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, much research has been devoted to studying SBEs and their various applications. [ 7,9–13 ] Among these studies, the removal of textile dyes by the adsorption technique, which appears to be relatively inexpensive and effective, is widely cited. [ 7,11,14–17 ]…”
Section: Introductionmentioning
confidence: 99%